Heart rate-index estimates oxygen uptake, energy expenditure and aerobic fitness in rugby players - Colosio, A. L.; Pedrinolla, A.; da Lozzo, G.; Pogliaghi, S. (Journal of Sports Science & Medicine, 2018)
The purpose of the study was to verify the suitability of heart rate-index (HRindex) in predicting submaximal oxygen consumption (VO2), energy expenditure (EE) and maximal oxygen consumption (VO2max) during treadmill running in rugby players. Fifteen professional rugby players (99.8 ± 12.7 kg, 1.85 ± 0.09 m) performed a running incremental test while VO2 (breath-by-breath) and heart rate (HR) were measured. HRindex was calculated (actual HR/resting HR) to predict submaximal and maximal VO2 ({[(HRindex x 6)-5.0] x (3.5 body weight)}) and EE. Measured and predicted VO2 and EE were compared by two-way RM-ANOVA (method, speed), correlation and Bland-Altman analysis. Measured and predicted VO2max were compared by paired t-test, correlation and Bland-Altman analysis. Submaximal VO2 and EE significantly increased (baseline VO2: 8.1 ± 1.6 ml·kg-1·min-1 VO2max: 46.8 ± 4.3 ml·kg-1·min-1, baseline EE: 0.03 ± 0.01 kcal·kg-1·min-1, peak EE: 0.23 ± 0.03 kcal·kg-1·min-1) as a function of speed (p < 0.001 and p < 0.001 for VO2 and EE respectively) yet measured and predicted values at equal treadmill speeds were not significantly different (p = 0.17; p = 0.16) and highly correlated (r = 0.95; r = 0.94). The Bland-Altman analysis confirmed a non-significant bias between measured and estimated VO2 (measured: 40.3 ± 10.7, estimated: 40.7 ± 10.1 ml·kg-1·min-1, bias = 1.35 ml·kg-1·min-1, z = 1.12, precision = 3.39 ml·kg-1·min-1) and EE (measured: 20.0 ± 0.05 kcal·kg-1·min-1, estimated: 20.0 ± 0.05 kcal·kg-1·min-1, bias = 0.00 kcal·kg-1·min-1, z = 0.04, precision = 0.02 kcal·kg-1·min-1). Estimated and predicted VO2max were not statistically different (p = 0.91), highly correlated (r = 0.96), and showed a non-significant bias (bias = 0.17, z = 0.22, precision = 1.29 ml·kg-1·min-1). HRindex is a valid field method to track VO2, EE and VO2max during running in rugby players.